PENGARUH MODEL PROBLEM BASED INSTRUCTION DENGAN MENGGUNAKAN MEDIA TANGRAM TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS V PADA MATERI PECAHAN SD NEGERI 51 SINGKAWANG - Dinar Dwi Prasetyo; Slamat Fitriyadi; Erdi Guna Utama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary school students’ mathematical creative thinking ability is the foundation for student to develop problem-solving abilities with differend and varied perspective. The study has importand objective, namely: 1) to determine the effect of the problem-based instruction learning model assisted by tangram media. 2) to determine the increase in mathematical creative thinking abilities with the problem-based instruction learning model assisted by tangram media. 3) to determine the implementation of the problem-based instruction learning model assisted by tangram media. This study uses an experimental method with post- test only design. The sample in this study that will be used is 15 students from class va as the experimental class and 15 studens as the control class. The type of research use is qualitative with experimental method methods and a Nonequivalent control group design research design. The total population of both classes is 47 with a random sampling technique. The prerequisite test uses the Shapiro Wilk Normality test and the Homogeneity test. Hypothesis testing uses the Independent sample t-test, Effect Size and implementation sheets. The results of the study showed 1) the average experimental post-test of 65.07 was higher than the average control post-test of 41.20. In addition, it can also be seen from the output of the Independent Sample t-test which has a significance value of Equal Variances Assumed of 0.001 <0.05. 2) the result of the Effect Size test was 1.673 which is in the very high criteria. 3) the assessment of the implementation observation sheet was 88% which is in the very high criteria.